Comparing Influence of Thermal Effects in Experimental Models - Thermotherapy in Medical Rehabilitation - Barbara Pietrzyk; Patrycja Dolibog; Tomasz Pryzwan; Klaudia Kierszniok (Rehabilitacja Medyczna)
Introduction: The subject of thermometry and impact of thermal effect on the human body is still a topic known and discussed in medical care. One of the basic methods in clinical diagnosis is the measurement of body temperature. In biological tissues, there are two main types of reactions caused by optical radiation: photochemical and thermal. The effects of radiation exposure depend on its properties and physical parameters, including the amount of absorbed dose and the duration of exposure. In the case of thermotherapy as a therapeutic method, the appropriate choice of radiation type and the selection of physical parameters is a necessary condition for obtaining desired, beneficial therapeutic effects. The aim of the study is to investigate the thermal effect of non-ionizing radiation: infrared (IR), ultraviolet (UV) and electromagnetic field (EMF) induced in short-wave diathermy (MD), measured with classical thermometers and a thermal imaging camera. The thermal effect, as a result of overheating with three different factors: IR, UV, MD; and under the same conditions, is studied. The variation in temperature distribution in different phantoms is evaluated in order to delve into the subject of thermal effect regarding each radiation separately and to consider its suitability for medical diagnosis and therapy.Material and methods: The thermal effect study was carried out on two phantoms. The first phantom F1 - a wooden cuboid (27.0 x 7.0 x 7.5cm) with five holes drilled at 5-cm intervals, into which thermometers were inserted (depth 5 cm). The second phantom - F2 was a biological tissue, the lower part of pork ham cut off along with the bone with fat covering and skin. Phantoms F1 and F2 were treated with an infrared heater (P1), a lamp emitting ultraviolet radiation (P2) and short-wave diathermy (P3); C and irradiation - 20 minutes, temperature measurements at intervals of 5 minutes, i.e. 5, 10, 15 and 20 minutes for the examined factors. During the experiment, temperature measurements were periodically made with the IR Thermal Radiometric Camera MobIR M3. For obtaining reliability of the measurements, the whole trial was repeated 10 times. Before the thermograms were made, two-hour intervals were applied between successive measurements, maintaining a constant ambient temperature of 23C.Results: With regard to UV radiation, there was an increase in the average temperature among the thermometers. This was particularly noticeable in the first thermometer with a 1.9% increase (up to 25.110.29C) above the ambient temperature (24.650.34C) after 15 minutes of measurements. After 20 minutes, the average temperature increase in thermometer 1 was 2.2% (up to 25.180.23C). A temperature increase in subsequent thermometers may be related to thermal conductivity and an increase of ambient temperature. In turn, for IR, an average 1.7% (to 25.160.87C) temperature increase of all thermometers was observed at 15 minutes and at 20 minutes, by 2.9% (to 25.481.35C) compared to baseline temperature (24.750.47\C). Comparing the average temperature of thermometer 1 with the ambient temperature (24.750.49C), the highest increase of 12.8% (to 27.930.69C) was noted after 20 minutes of measurements. In diathermy, after 10 minutes, an increase in the average temperature in thermometer 1 was observed by 2.8% (to 25.690.46C) above the ambient temperature. The highest increase in average temperature was recorded in thermometers 1 and 5 in the 20thminute of measurements.Conclusions: All of the applied methods caused temperature increases in the used phantoms. The temperature distribution in the wooden phantom corresponds to that in the biological tissue for the interaction of infrared radiation (IR) and short-wave diathermy (MD), which was confirmed by thermovision. The increase in the internal temperature of the superheated biological structure corresponds to the increase in the distribution of the phantom’s internal temperature.